Factor affecting severe atherothrombotic cerebral infarction in patients with type 2 diabetes mellitus: Large‐scale claim database analysis of Japan - Takeshi Horii; Yoichi Oikawa; Kasumi Kidowaki; Akira Shimada; Kiyoshi Mihara (Journal of Diabetes Investigation)
ABSTRACT Aims This study aimed to investigate the factors associated with the exacerbation of the severity of atherothrombotic brain infarction at discharge in patients with type 2 diabetes using a large‐scale claims database. Materials and Methods This retrospective cross‐sectional study utilized the Medical Data Vision administrative claims database, a nationwide database in Japan using acute care hospital data, and the Diagnosis Procedure Combination system. Diagnosis Procedure Combination data collected between April 1, 2008, and December 31, 2022, were extracted. Patients with type 2 diabetes were included. Severe atherothrombotic brain infarction was defined as a modified Rankin scale score of ≥3. Results Severe atherothrombotic brain infarction occurred in 43,916/99,864 (44.0%) patients with type 2 diabetes. The odds ratio for severe atherothrombotic brain infarction increased significantly per 10 year increments in age (odds ratio: 1.69, 95% confidence interval: 1.66–1.71). A body mass index of <25 kg/m2, with a body mass index of ≥25 kg/m2 as reference, also increased the risk for severe atherothrombotic brain infarction (odds ratio: 1.11, 95% confidence interval: 1.08–1.15). The odds ratios in insulin and dipeptidyl peptidase 4 inhibitor use were significantly higher than 1. In particular, statin use (odds ratio: 0.85, 95% confidence interval: 0.83–0.88), fibrate use (odds ratio: 0.68, 95% confidence interval: 0.59–0.78), aspirin use (odds ratio: 0.78, 95% confidence interval: 0.75–0.80), and P2Y12 inhibitor use (odds ratio: 0.88, 95% confidence interval: 0.85–0.91) were associated with a lower odds ratio for severe atherothrombotic brain infarction. Conclusions The active management of lipid levels using statins and fibrates may be beneficial in preventing the exacerbation of atherothrombotic brain infarction in type 2 diabetes patients.